PENGARUH KUALITAS PRODUK , CITRA MEREK ,HARGA, DAN PROMOSI, TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK HONDA DI KOTA MEDAN - Bunga Aditi; H M Hermansyur (Universitas Medan Area, 2017)
This study aims to identify and explain the effect of price, promotion and distribution channel partially and simultaneously on purchasing decisions. This type of research is explanatory research with quantitative approach. The population of this research is the Honda brand car buyers in the city of Medan with a total sample of 100 people by using simple random sampling technique, questionnaire data used is Multiple Regression.The results showed that the variable product quality, brand image, price and promotion together significantly influence purchasing decisions.T test results showed that each - each variable product quality, brand image, price and promotion jointly significant effect on purchasing decisions.The company should be able to inform the Honda brand car with a better understanding of the variable product quality, brand image, Price and promotion through the sales conversations, so that they are understood in marketing their products.Keywords: product quality, brand image, pricing and promotions, and Purchase Decision